Acute Brain Ischemia, Infarction and Hemorrhage in Subjects Dying with or Without Autopsy-Proven Acute Pneumonia - Beach, Thomas G; Sue, Lucia I; Intorcia, Anthony J; Glass, Michael J; Walker, Jessica E; Arce, Richard; Nelson, Courtney M; Serrano, Geidy E (medRxiv : the preprint server for health sciences, 2021)
Stroke is one of the most serious complications of Covid-19 disease but it is still unclear whether stroke is more common with Covid-19 pneumonia as compared to non-Covid-19 pneumonia. We investigated the concurrence rate of autopsy-confirmed acute brain ischemia, acute brain infarction and acute brain hemorrhage with autopsy-proven acute non-Covid pneumonia in consecutive autopsies in the Arizona Study of Aging and Neurodegenerative Disorders (AZSAND), a longitudinal clinicopathological study of normal aging and neurodegenerative diseases. Of 691 subjects with a mean age of 83.4 years, acute pneumonia was histopathologically diagnosed in 343 (49.6%); the concurrence rates for histopathologically-confirmed acute ischemia, acute infarction or subacute infarction was 14% and did not differ between pneumonia and non-pneumonia groups while the rates of acute brain hemorrhage were 1.4% and 2.0% of those with or without acute pneumonia, respectively. In comparison, in reviews of Covid-19 publications, reported clinically-determined rates of acute brain infarction range from 0.5% to 20% while rates of acute brain hemorrhage range from 0.13% to 2%. In reviews of Covid-19 autopsy studies, concurrence rates for both acute brain infarction and acute brain hemorrhage average about 10%. Covid-19 pneumonia and non-Covid-19 pneumonia may have similar risks tor concurrent acute brain infarction and acute brain hemorrhage when pneumonia is severe enough to cause death. Additionally, acute brain ischemia, infarction or hemorrhage may not be more common in subjects dying of acute pneumonia than in subjects dying without acute pneumonia.